Transcutaneous electrical acupoint stimulation (TEAS) for cancer-related fatigue: study protocol for a systematic review and meta-analysis - Zhihan Chen; Yulan Ren; Yiwei Zeng; Jialin Xia; Xiaoping Tian (BMJ Open, 2021)
Introduction Cancer-related fatigue (CRF) is a prevalent symptom in cancer survivors. Transcutaneous electrical acupoint stimulation (TEAS) has been reported as a promising therapy for CRF. This protocol is proposed for a systematic review that aims to assess the efficacy and safety of TEAS for CRF.Methods and analysis Cochrane Central Register of Controlled Trials, PubMed, Medline, Embase, Chinese National Knowledge Infrastructure, VIP, Wanfang database, Chinese Biomedical Literature Database, Chinese Clinical Trial Registry System, ClinicalTrials.gov and WHO International Clinical Trial Registry Platform will be searched from inception to 31 January 2021 without language limitations. The eligible randomised controlled trials will be included. The primary outcomes include changes in the revised Piper fatigue scale, the Brief fatigue inventory, the Multidimensional fatigue inventory and the Functional assessment of chronic illness therapy fatigue. The secondary outcomes are the quality-of-life measurement index, the Hamilton anxiety scale, the Hamilton depression scale and adverse events. The selection of studies, data extraction and assessment of risk of bias will be conducted independently by two reviewers. Data synthesis will be performed using RevMan V.5.4.1. The quality of evidence will be evaluated with the Grading of Recommendations, Assessment, Development and Evaluation system. This study will strictly adhere to the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines.Ethics and dissemination Ethical approval is not required as this is a systematic review and meta-analysis based on previously published studies involving no private information of patients. The results of this study will be disseminated in a peer-reviewed journal.PROSPERO registration number CRD42020220282.